Image and influence : studies in the sociology of film - Tudor, Andrew, 1942- (London : Routledge, 2014)
This text outlines what sociologists need to know of the nature of communication and of mass culture, while also looking in some empirical detail at the workings of the Hollywood community and the psychology of the star system. It explores trends such as attempts to adapt semiology and psycholinguistics to our understanding of film'language', using them to develop a paradigm for film analysis. The book goes on to offer a guide to comprehension of the relation between cinema and society through detailed analysis of the relation between the German silent cinema and its social context and ext.
Keywords: Motion pictures -- Social aspects